Multifunctional chitosan magnetic-graphene (CMG) nanoparticles: a theranostic platform for tumor-targeted co-delivery of drugs, genes and MRI contrast agents - Wang, Chunyan; Ravi, Sowndharya; Garapati, Ujjwala Sree; Das, Mahasweta; Howell, Mark; Mallela, Jaya; Alwarappan, Subbiah; Mohapatra, Shyam S.; Mohapatra, Subhra (Journal of materials chemistry. B, Materials for biology and medicine, 2013)
Combing chemotherapy with gene therapy has been one of the most promising strategies for the treatment of cancer. The noninvasive MRI with superparamagnetic iron oxide (SPIO) as contrast agent is one of the most effecitve techniques for evaluating the antitumor therapy. However, to construct a single system that can deliver efficiently gene, drug and SPIO to the cancer site remains a challenge. Herein, we report a chitosan functionalized magnetic graphene nanoparticle (CMG) platform for simultaneous gene/drug and SPIO delivery to tumor. The phantom and ex vivo MRI images suggest CMG as a strong T contrast-enhancing agent. The CMGs are biocompatible as evaluated by the WST assay and predominantly accumulate in tumors as shown by biodistribution studies and MRI. The anticancer drug doxorubicin (DOX) loaded CMGs (DOX-CMGs) release DOX faster at pH 5.1 than at pH 7.4, and more effective (IC50 = 2 μM) in killing A549 lung cancer cells than free DOX (IC50 = 4 μM). CMGs efficiently deliver DNA into A549 lung cancer cells and C42b prostate cancer cells. In addition, i.v. administration of GFP-plasmid encapsulated within DOX-CMGs into tumor-bearing mice has showed both GFP expression and DOX accumulation at the tumor site at 24 and 48 hrs after administration. These results indicate CMGs provide a robust and safe theranostic platform, which integrates targeted delivery of both gene medicine and chemotherapeutic drug(s), and enhanced MR imaging of tumors. The integrated chemo- and gene- therapeutic and diagnostic design of CMG nanoparticles shows promise for simultaneous targeted imaging, drug delivery and real -time monitoring of therapeutic effect for cancer.